Ant community and habitat limit colony establishment by the fire ant, Solenopsis invicta. (16th November 2016) - Tschinkel, Walter R.; King, Joshua R.
Summary: Hypotheses of community assembly include limitation through habitat physical attributes, as well as competition among species. Such hypotheses must be resolved through experimental tests. Previous experiments have shown that: (i) fire ants of the monogyne social form occur mostly in highly disturbed habitat where they do not compete with mature colonies of co‐occurring ants; (ii) in native pine forests of northern Florida, habitat disturbance favours fire ants while simultaneously reducing native ants; (iii) fire ants thrive in these disturbances but do not persist as these become less disturbed over time; and finally, (iv) newly mated, dispersing/colony‐founding fire ant queens settle preferentially in such disturbed sites. We now show that by choosing disturbed sites, newly mated, monogyne fire ant queens greatly increase their chances of successful colony establishment. Experimental plots were created in the native ground cover of a north Florida pine forest with all combinations of tilling, shading or reduction of the native ant community. Newly mated fire ant queens, incipient colonies and small colonies were planted in these plots. Only five of 980 (0·5%) newly mated queen nests survived after 120 days, and only five of 400 incipient colonies (1·3%) survived after 30 days. All survivors were in plots with tilling and/or native ant reduction. Extrapolation indicated that 0·04% of newly mated queens and 0·1% of incipient colonies were likely to have survived at 1 year. In contrast, planting small colonies resulted in much higher rates of survival – in plots with native ant reduction, fire ants increased on baits throughout the year but decreased in unreduced control plots. Fifteen months after planting 108 colonies, 21 mounds (19%) were found in the ant‐reduced plots, but <2% of 108 colonies survived in the control plots. Taken together, these results show that by landing in disturbed habitat with its reduced native ant population, newly mated fire ants queens increase their chances of successful colony establishment. In contrast to much of the previous literature, our results suggest that ant community assembly proceeds primarily by queen habitat choice and secondarily by filtering and competition. A lay summary is available for this article. Abstract : Lay Summary